Analysis of local budgets revenues in the Republic of Moldova: level, structure and dynamics for 2008-2014 years - Andrei PETROIA (Eastern European Journal of Regional Studies, 2015)
This paper consist largely of analysis of the local budgets revenues of the Republic of Moldova for the period of 2008-2014. The analysis can not offer many information in dynamics due to the few number of years, but we tried to make an analyze of the situation. Informational support of the work are the laws and regulations of the country; data provided by the Ministry of Finance, National Bureau of Statistics and the literature. The purpose of this paper is to approach each category of income and part of it, the time evolution of local budget revenues over several consecutive years of budget income distribution in the directions of the Republic of Moldova, and analysis of each component of the local budget. In this paper, we have analyzed in dynamics structure in total revenues of local budgets, in national public budget, in state budget and in GDP. The main components analyzed were: tax and non-tax revenues, revenues without grants and transfers, grants and transfers from the state budget. Also we have attracted special attention to direct and indirect taxes, as well as their components.The necessity of this study is to present a clear and concise form of the administrative-territorial units' budget feature, conceptual notions, policies which are reflected on local revenues in Moldova. This paper aims possibility of revising the budget system structure, improve financial relations within it and its evolution, but it does not reflect fully all matters related to the budget system.